1997
DOI: 10.5860/crl.58.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Toward a TQM Paradigm: Using SERVQUAL to Measure Library Service Quality

Abstract: This study provides the results of a survey conducted in the fall of 1994 by the Sterling C. Evans Library to measure service quality. This general user survey provided feedback from customers on their minimum, perceived, and desired levels of service from an academic library. The devised measuring instrument is based on SERVQUAL, a service quality survey created by Leonard L. Berry, A. Parasuraman, and Valarie A. Zeithaml. The SERVQUAL survey is designed to measure service quality in five dimensions: tangible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 3 publications
1
18
0
4
Order By: Relevance
“…This lit erature has provided initial guidance in defining library service quality and clari fying the conceptual framework for ser vice delivery improvements. Recent re search on academic libraries, based on this literature, has been conducted by Vicki Coleman, Yi Xiao, Linda Blair, and Bill Chollett, 7 Susan Edwards and M. Browne, 8 Hernon and Calvert, 9 Nitecki, 10 and White and Abels. 11 In these studies, the five-di mensional SERVQUAL model and the twenty-two-item scale proposed by A. Parasuraman, Leonard Berry, and Valarie Zeithaml 12 are prominent.…”
mentioning
confidence: 99%
“…This lit erature has provided initial guidance in defining library service quality and clari fying the conceptual framework for ser vice delivery improvements. Recent re search on academic libraries, based on this literature, has been conducted by Vicki Coleman, Yi Xiao, Linda Blair, and Bill Chollett, 7 Susan Edwards and M. Browne, 8 Hernon and Calvert, 9 Nitecki, 10 and White and Abels. 11 In these studies, the five-di mensional SERVQUAL model and the twenty-two-item scale proposed by A. Parasuraman, Leonard Berry, and Valarie Zeithaml 12 are prominent.…”
mentioning
confidence: 99%
“…Measures of reliability have been a significant part of LibQUALϩ ⌻⌴ , the tool developed by the Association of Research Libraries to assess service quality, and its business world predecessor, SERVQUAL. Research employing these tools has demonstrated that a library's ability to reliably deliver promised services, including the accuracy of the check-in process, is crucial in the minds of users Cook, Heath, and Thompson 2001;Nitecki and Hernon 2000;Coleman et al 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This instrument has been designed and validated for use in a variety of service encounters. In addition, many investigators have adapted the SERVQUAL measures to evaluate the service quality of libraries (White and Abels 1995;Nitecki 1996;Rowley 1996;Coleman et al 1997).…”
Section: Service Support Systemmentioning
confidence: 99%